Hypertonic Saline Solution for Signal Transmission and Steering in MRI-Guided Intravascular Catheterisation - Caenazzo, Alberto; Althoefer, Kaspar (Towards Autonomous Robotic Systems, 2018)
Use of traditional low-impedance sensor leads is highly undesirable in intravascular catheters to be used with MRI guidance; thermal safety and quality of imaging are particularly impacted by these components. In this paper, we are showing that hypertonic saline solution, a high-impedance body-like fluid, could be a compatible and effective signal transmission medium when used in MRI-compatible catheters. We also propose a simple type of catheter design that can be steered hydraulically using the same saline solution. Integration of hydraulic steering is not required for MRI-compatibility; however efficient design can bring advantages in terms of structural simplicity and miniaturisation. Manufacturing of proof-of-concept prototypes using 3D printing is underway.